Preliminary findings of a previously unrecognized porcine primary immunodeficiency disorder - Cino Ozuna, Ada Giselle; Rowland, Raymond R. R.; Nietfeld, Jerome C.; Kerrigan, Maureen A.; Dekkers, Jack C. M.; Wyatt, Carol R. (My University, 2012)
Weaned pigs from a line bred for increased feed efficiency were enrolled in a study of the role of host genes in the response to infection with Porcine Reproductive and Respiratory Syndrome Virus (PRRSV). However, 4 of the pigs were euthanized early in the study due to weight loss with poor body condition and illness; 2 pigs, before PRRSV infection, and the other 2, approximately 2 weeks after virus inoculation. The 2 inoculated pigs failed to produce PRRSV-specific antibodies. Gross findings included pneumonia, absence of a detectable thymus, and small secondary lymphoid tissues. Histologically, lymph nodes, spleen, tonsils, and Peyer’s patches were sparsely cellular with decreased to absent T and B lymphocytes.
Keywords: Clinical pathology; Immunohistochemistry; Lymphoid tissues; Pig diseases; Primary immunodeficiency